Attitude-Based Coalition Towards Policy-Driven Policies "Coalition: Eight Parliamentary Parties And An Open Proportional System In The 2024 Elections" - Dinda Rembulan (Jurnal Indonesia Sosial Teknologi, 2023)
This journal discusses the formation of a coalition involving eight parliamentary political parties: the Golongan Karya Party (Golkar), the Great Indonesia Movement Party (Gerindra), the National Democratic Party (Nasdem), the Nation Awakening Party (PKB), the Democratic Party, the Prosperous Justice Party (PKS), the National Mandate Party (PAN), and the United Development Party (PPP). The coalition is based on their shared stance to maintain the application of the proportional open electoral system in the 2024 election. In this context, the study refers to William Gamson's theory of determining factors for a coalition, which consists of three types. Firstly, the initial distribution of resources is a crucial factor where all coalition participants calculate opportunities deemed more rational to favor those perceived to possess the most significant or determining resources. Secondly, the rewards obtained factor into the decision-making process, where coalition participants evaluate options expected to yield the maximum reciprocity or advantage. Finally, the decision point factor plays a role, as the most effective decision is based on the strength of resources possessed by each coalition participant. The research adopts a qualitative method supported by literature study techniques to obtain data. The results of this study reveal that the coalition formed among the eight parliamentary political parties is based on the calculation made by each party, considering that the implementation of the open proportional electoral system is more rational, provides advantages, and is perceived as more effective in supporting their winning efforts in the 2024 election.